Medication adherence among hypertensive patients in primary care clinics in Sarawak, Malaysia : a mixed-methods study - Chor Yau, Ooi; R., Ramli; Y. C., Liu; Kamarudin, Kana; Imam Bux, Brohi; Sabrina, Lukas; Juslina, Omar; Rafidah, Elias (2025)
Hypertension affects 30-40% of people globally, with nearly half of hypertensive patients in Malaysia having uncontrolled blood pressure due to poor medication adherence. Factors influencing adherence include polypharmacy, medication knowledge, ethnicity, side-effects, traditional medicine use and socio-economic. While most studies focus on West Malaysia, there is limited research in Sarawak, highlighting the need for a mixedmethods study to explore medication adherence in this region.This study used a mixed-methods explanatory sequential design in government health clinics with hypertensive patients. The quantitative phase assessed medication adherence and associated factors using the MedicationComplianceAssessment Form. The qualitative phase involved in-depth interviews to explore factors affecting adherence identified in the quantitative phase. Quantitative data were analysed with means, percentages, and logistic regression, while qualitative data were analysed thematically.Quantitative study with 548 hypertensive patients from 23 health clinics found that 40% were male, Bidayuh ethnicity (43.6%) with mean age of 58.6 SD 11.34 years. About half (58.6%) had wellcontrolled hypertension, while 32.3% were non-adherent to their medication. Uncontrolled blood pressure was significantly associated with non-adherence (p=0.001, OR: 1.83, 95% CI: 1.27-2.63). Factors influencing adherence included age (p=0.035, OR: 0.98, 95% CI: 0.97-0.99) and taking multiple medications (p=0.002, OR: 1.55, 95% CI: 1.18-2.05). Qualitative interviews with 24 patients revealed that age improved understanding but increased forgetfulness, impacting adherence both ways, while managing multiple medications led to frustration and confusion, hindering adherence.This study highlights key factors affecting medication adherence in Sarawak, including age and polypharmacy, suggesting the need for targeted interventions to improve adherence.